Cyber Public Relations dalam Pembentukan Branding â€œDesa Wisataâ€ di Sidomulyo Kabupaten Jember - Minan Jauhari (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2022)
This article places cyber public relations as a perspective in understanding organizational communication activities carried out by the Sidomulyo village government, by utilizing internet technology tools and cyber media as a new space in the context of establishing the